Will they stay or will they go?: The political influence of GM-averse importing companies on biosafety decision makers in Africa - Gruère, Guillaume P.; Takeshima, Hiroyuki (Wiley, 2012)
Presumed but unproven trade risks are considered a significant factor in the reluctance of African countries to use potentially beneficial genetically modified (GM) crops. We model a threat from an importer to a local policy maker announcing an upcoming confined field trial of a GM crop as a dynamic game of incomplete information and illustrate our analysis with a stochastic simulation. The results show that provided the cost of threatening is small, and the cost of going out of the country is significant, the importer will threaten to go out and may effectively lower the probability of commercializing a GM crop.